1965
DOI: 10.1536/ihj.6.367
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Changes in Rheumatoid Arthritis

Abstract: To evaluate the significance of heart changes in rheumatoid arthritis, ST-T changes of electrocardiogram in healthy control were studied. It was significantly less frequently observed in the control group than in rheumatoid patient group. HIS report deals with the incidence of electrocardiographic abnormalities in the control group as compared with previously reported incidence of heart changes in rheumatoid patients.1),2) Following results had been confirmed by the author: Among 158 patients with rheumatoid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0
2

Year Published

1967
1967
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
3
0
0
2
Order By: Relevance
“…29 Masooleh et al and Asai K et al found 15% and 20.9% had ST changes respectively. 25,30 Second most common finding in our study was right bundle branch block (7.1%) which was comparable to findings of other studies. 25,29,30 Sinus bradycardia was not found in any patient as was similarly reported by other studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…29 Masooleh et al and Asai K et al found 15% and 20.9% had ST changes respectively. 25,30 Second most common finding in our study was right bundle branch block (7.1%) which was comparable to findings of other studies. 25,29,30 Sinus bradycardia was not found in any patient as was similarly reported by other studies.…”
Section: Discussionsupporting
confidence: 92%
“…25,30 Second most common finding in our study was right bundle branch block (7.1%) which was comparable to findings of other studies. 25,29,30 Sinus bradycardia was not found in any patient as was similarly reported by other studies. 25,29 Most common echocardiographic abnormality was LV diastolic dysfunction found in 42.2% cases of rheumatoid arthritis as compared to only 4.3% among controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…"Συχνότερα τών υποκειμενικών συμπτωμάτων εΐναι ή άνεύρεσις αντικει μενικών κλινικών ή εργαστηριακών σημείων καρδιοπάθειας, τα οποία δυνατόν να υπάρχουν πολύ ένωρίτερον. Ούτω παθολογικοί καρδιακοί τόνοι και φυσή ματα παρατηρούνται εις σχετικώς ύψηλόν ποσοστόν (20% περίπου) 5 .…”
Section: παθολογική ανατομίαunclassified
“…Αί μεγαλύτεραι σειραί παθολογοανατομικώς μελετηθέντων ασθενών μέ ρευματοειδή αρθρίτιδα, οΐτινες ένεφάνισαν αλλοιώσεις εκ τής καρδίας είς ύ-ψηλήν σχετικώς συχνότητα, έδημοσιεύθησαν υπό τών ßaggenstos και Rosenberg (1941), Young και Schwedel (1944), Bywaters (1950), Cruickshank (1958), Lebowitz (1963), Sokoloff (1964) 134 • Ή διαφορά αΰτη πιθανώς οφείλεται αφ' ενός μεν είς την ελλειψιν ειδι κών κλινικών ευρημάτων εκ της καρδίας χαρακτηριστικών της ρευματοειδούς άρθρίτιδος, άφ' ετέρου δε είς την υπό πολλών Ιατρών άπόδοσιν τών διαπιστου μένων καρδιακών εκδηλώσεων είς αλλάς αιτίας. 5 Εξ άλλου ή μακρά κατάκλισις τών ασθενών αυτών ώς και ή χρονία λήψις αναλγητικών καί άντιφλεγμονωδών φαρμάκοον εμποδίζουν την έκδήλωσιν πλείστων καρδιακών συμπτωμάτων !32 . Συχνότερον προσβάλλεται ή καρδία επί τών βαρύτερων μορφών της νό σου μετά θετικής αής όροαντιδράσεως δια τον ρευματοειδή παράγοντα, επί πυλυαρθρι.κής ή επί μονοαρθρικής εντοπίσεως ταύτης, επί υπάρξεως υποδορίων οζιδίων καί επισκληρίτιδος ή οσάκις υφίσταται καί ετέρα σπλαγχνική εντόπισις ρευματοειδούς φύσεως 20, 32, 51> 74, 129 .…”
unclassified